VARKonstruct: innovating sustainable education in construction technology through adaptive e-learning - Mohd Noor, Siti Nur Aishah; Ramly, Mohd Khairul Amri (2025)
The construction sector is quickly evolving through technological integration in education; yet, conventional methods frequently overlook diverse learning preferences, resulting in inconsistent educational outcomes. 'VARKonstruct: Innovating Sustainable Education in Construction Technology through Adaptive E-Learning' tackles this issue by incorporating the VARK learning styles model (Visual, Auditory, Reading/Writing, Kinesthetic) with customized e-learning tools to promote a more inclusive and engaging educational atmosphere. The approach utilizes immersive simulations, interactive laboratories, and multimedia resources to deliver a tailored educational experience that corresponds with each student's primary learning preference. This adaptive method fits personal learning preferences and mitigates educational inequities by democratizing access to varied learning resources. Preliminary results suggest that VARKonstruct significantly improves understanding and retention by enabling learners to interact with intricate construction concepts via their preferred learning modality, therefore cultivating more proficient and motivated workers prepared to address industry requirements. Moreover, the project emphasizes the significance of sustainable education through the use of digital platforms that reduce resource consumption while enhancing learning effectiveness. It is advisable to implement data-driven learning analytics to enhance personalized learning pathways and evaluate student progress, while also broadening VARKonstruct's application to additional STEM fields to foster sustainable educational practices that empower both educators and learners.